2011
DOI: 10.1111/j.1740-8261.2010.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Popliteal and Mesenteric Computed Tomography Lymphangiography of the Canine Thoracic Duct

Abstract: Thoracic duct computed tomography (CT) lymphangiograms were performed on seven clinically normal dogs. The appearance of the thoracic duct system was compared following administration of contrast medium through a mesenteric lymphatic vessel vs. ultrasound guided percutaneous injection into a popliteal lymph node using helical and sequential CT acquisition modes. The number of visible thoracic duct branches and the largest thoracic duct branch cross-sectional area and mean Hounsfield units (HU) were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
(33 reference statements)
0
31
0
Order By: Relevance
“…[37][38][39][40][41] Two basic approaches have been described: popliteal lymph node injection and mesenteric lymph node injection. However, the thoracic duct commonly has multiple tributaries, so that identifying the location of a common duct before branching is useful for presurgical planning.…”
Section: Ultrasound-guided Computed Tomography and Radiographic Lymphmentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39][40][41] Two basic approaches have been described: popliteal lymph node injection and mesenteric lymph node injection. However, the thoracic duct commonly has multiple tributaries, so that identifying the location of a common duct before branching is useful for presurgical planning.…”
Section: Ultrasound-guided Computed Tomography and Radiographic Lymphmentioning
confidence: 99%
“…26 The most common complication was leakage of contrast material through the needle tract, which occurred in 8 of 18 studies and rendered 5 studies nondiagnostic. 41 A common theme from these investigations is the variation in number of thoracic duct branches, and their size and location, which is essential information for presurgical planning and identification of complete ductal ligation following surgery. PV SV A compared the two techniques and concluded that popliteal injection was faster and less painful than mesenteric injections for CT thoracic duct lymphangiography.…”
Section: Antegrade Pyelography and Pyelocentesismentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike conventional methods requiring procedural experience, in present method, it is possible to obtain a better understanding of individual differences in the thoracic duct more easily. Direct administration into the popliteal lymph node in a hind leg, which has recently been reported, is less invasive because it only involves injection into subcutaneous lymph nodes [9,10], but these lymph nodes are small and mobile, meaning that a certain amount of experience is required for administration at this site. Unlike conventional methods requiring procedural experience, in the experiments in the present study, angiography contrast medium, used clinically on an everyday basis, was injected beneath the rectal membranes continuous with the anus and the vaginal membranes continuous with the vulva, as well as into perianal tissue, all sites that are easy to approach.…”
mentioning
confidence: 99%
“…The position and course of the thoracic duct and cisterna chyli must be confirmed preoperatively when thoracic duct ligation or cisterna chyli ablation is performed, for which lymphography of the thoracic duct is of course required [1]. Current methods for performing lymphography of the thoracic duct involve the injection of contrast medium into the mesenteric lymph nodes during laparotomy under anesthesia or contrast imaging of the thoracic duct after the injection of contrast medium into the popliteal lymph node of a pelvic limb [2,9,10]. However, laparotomy is an invasive procedure, and reliable results cannot be obtained by percutaneous penetration of lymph nodes when the size and position of these lymph nodes are undetermined.…”
mentioning
confidence: 99%